Emerald city : the birth and evolution of an Indian gemstone industry - Babb, Lawrence A. (New delhi Aditya Prakashan, 2013)
"A study of the contemporary gemstone industry of Jaipur with special emphasis on its ownership class. Detailed examination of an industry in a non-Western setting, with contextual background for the Jain religion and recent Jaipur history"--Provided by publisher.
Dramatis personae : industrial multiculturalism -- The rise of the emerald elite -- Doing business -- Contexts -- The decline of the emerald elite.
Includes bibliographical references (p. 201-204) and index.
Keywords: Precious stone industry -- India -- Jaipur; Ethnology -- India -- Jaipur